The Labour Party: A Marxist History - Pette, Martin (Labour / Le Travail, 1991)
The article reviews the book, "The Labour Party: A Marxist History," by Tony Cliff and Donny Gluckstein.
Keywords: BOOKS – Reviews; FINE; Sidney; Nonfiction; VIOLENCE in the Model City: The Cavanaugh Administration; Race Relations & the Detroit Riot of 1967 (Book); violence